Recent progress in patent foramen ovale and related neurological diseases: A narrative review - Shi, Fanfan; Sha, Leihao; Li, Hua; Tang, Yusha; Huang, Litao; Liu, Huizhen; Li, Xu; Li, Lin; Yang, Wenjie; Kang, Deying; Chen, Lei (Frontiers in Neurology, 2023)
Patent foramen ovale (PFO) is a common congenital cardiac abnormality when the physiological channel of atrioventricular septal is not closed at adulthood. This abnormality affects 25% of the general population. With development of precision medicine, an increasing number of clinical studies have reported that PFO is closely related to various neurological diseases such as stroke, migraine, obstructive sleep apnea, and decompression syndrome. It has also been suggested that PFO closure could be effective for treating these neurological diseases. Therefore, increasing attention has been given to the prevention, diagnosis, and treatment of PFO-related neurological diseases. This article reviewed and discussed the pathogenesis, epidemiology and clinical characteristics of PFO-related neurological diseases, as well as the treatment of different neurological diseases. By reviewing existing literature, this paper aims to provide current progress for this field and decision-making evidence for clinical practice.